The Assessment of Neurosensory Disturbance Following Bilateral Sagittal Split Osteotomy With Subjective and Three-Dimensional Evaluation - (:unkn) unknown (My University, 2021)
PURPOSE: Inferior alveolar neurosensory disturbance (IAND) is the most common complication of bilateral sagittal split osteotomy (BSSO). The aim of the present study was to evaluate IAND with subjective tests postoperatively and assess the relationship between three-dimensional measurements of the mandibular canal (MC) and IAND. METHODS: Eighteen patients (Mean age: 24.05 ± 5.85 years) treated with BSSO were retrieved from the archive. Subjective tests (light touch, tactile sensitivity, 2-point discrimination, brush-stroke directional discrimination, sharp/blunt discrimination, dental vitality, questionnaire) and three-dimensional measurements related to MC and fixation screws were done postoperatively (on average 20.43 ± 8.76 months after surgery). Statistical significance was set at P < 0.05. RESULTS: Subjective test results were found compatible with each other except brush-stroke directional discrimination test. According to the questionnaire, IAND was apparent in all patients immediately after surgery, and recovery after 1 to 2 years was statistically significant (P < 0.05). Preoperative ramus width, medial and lateral cancellous bone lengths, the decrease in MC length, and the presence of screw in MC were not related to IAND (P < 0.05). CONCLUSIONS: There is a high incidence of IAND following BSSO, and the subjective tests are efficient to evaluate the disturbance. Spontaneous recovery of the nerve occurs during the follow-up periods. Instead of preoperative measurements of bone thickness, MC length, and the position of fixation screws, the surgical procedure seems to be more important in IAND occurrence.